Gerak Dasar Tari Untuk Anak Usia Dini - Hilda Zahra Lubis; Ijar Salna; Lu’Lu Rahmadanti; Annisa Nur Faudillah (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Art, as an important part of human life, also plays an important role in early childhood education, which aims to foster various developmental skills. Everyday movements help children's physical development by improving their motor skills. Gross and fine motor development are known to be part of children's motor development. Therefore, it is very important for children's gross motor development to understand dance movements, to foster an attitude of appreciating art by allowing children to express themselves and appreciate various artistic media. This essay aims to explain how the development of early childhood gross motor skills is helped by learning basic dance movements.